“I Am a Puzzle”: Adolescence as Reflected in Self-Metaphors - Larsen, Denise J.; Larsen, Janine E. (Canadian Journal of Counselling and Psychotherapy, 2007)
Given growing interest in narrative counselling, narrative theories of the self have received much attention. In this study, adolescents describe self through the construction of self-metaphors. The project explores the relationship between narrative developmental assumptions and the adolescents’ own self descriptions. Three themes are revealed: (a) multiple self(ves), (b) self as complex, and (c) embodying hope. The adolescents’ self-portrayals reflect assumptions present in both traditional and narrative developmental theories. Hope emerges as an implicit aspect of self. Further, self-metaphor construction proves to be a task of fruitful self-reflection. Implications for counselling and school guidance are discussed.